STUNTING TODDLER RECOVERY FOOD MAKING TRAINING - Chabibah, Nur; Kristiyanti, Rini; Ari Susiatmi, Sandi (Batik-MU : Jurnal Pengabdian Masyarakat, 2023)
The prevalence of stunting is still high in Indonesia. The involvement of cadres is needed to support the recovery of stunted toddlers, especially in assisting mothers and families in providing additional food for the recovery of stunted toddlers. Community Service aims to increase the knowledge and skills of cadres in preparing and providing recovery food for stunting toddlers. The method used in this community service is a discussion using the brainstorming method with the media of match cards and demonstrations of cooking practices. The six-month activity in three villages, namely Tangkil Tengah , Kedungpatangewu and Rengas Village with 63 participants. The activity went smoothly with the result that there was an increase in cadres' understanding of lactation management where the written evaluation score obtained an average pre-test of 78.00 and an average post-test score of 90.00. The high calorie and protein menu that was cooked in this activity was fish nuggets and brownies milk avocado pudding (alubow). In conclusion, after the community service was carried out, health cadres supported by the village and the Kedungwuni II Health Center are committed to continuing to provide recovery food for stunting toddlers and making recovery food guidebooks for stunting toddlers.